2022
DOI: 10.1021/acs.jced.2c00357
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Behavior and the Mechanism of HCl Gas in Four [EMIM]Cl-Based Deep Eutectic Solvents

Abstract: The solubility behavior of HCl gas in four 1-ethyl-3-methylimidazolium chloride([Emim]Cl)-based deep eutectic solvents (DESs), i.e., an [Emim]Cl mixture with 4-methylimidazole (DES1), 2-methylimidazole (DES2), malonic acid (DES3), and poly(ethylene glycol) 400 (DES4), was studied at 301.15−348.15 K and a 0−101.325 kPa partial pressure of HCl. The H-bonding interaction and the dissolution mechanism were studied via Fourier-transform infrared spectroscopy (FTIR), 1 H NMR, and 13 C NMR. The HCl solubility increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…An attractive complementary approach would be a technique that combines the superior safety profile of hydrochloric acid with the advantageous reactivity and electrochemical properties of gaseous hydrogen chloride. Although ionic liquids ( 23 25 ) and metal-organic frameworks ( 26 ) for the reversible absorption of HCl are reported, none of them were used as scalable storages that can directly be used for hydrochlorination reactions and electrolysis. Recently, Geng and coworkers ( 27 ) demonstrated that imidazole-based deep eutectic solvents can be used for the efficient coupling of HCl capture and conversion.…”
Section: Introductionmentioning
confidence: 99%
“…An attractive complementary approach would be a technique that combines the superior safety profile of hydrochloric acid with the advantageous reactivity and electrochemical properties of gaseous hydrogen chloride. Although ionic liquids ( 23 25 ) and metal-organic frameworks ( 26 ) for the reversible absorption of HCl are reported, none of them were used as scalable storages that can directly be used for hydrochlorination reactions and electrolysis. Recently, Geng and coworkers ( 27 ) demonstrated that imidazole-based deep eutectic solvents can be used for the efficient coupling of HCl capture and conversion.…”
Section: Introductionmentioning
confidence: 99%
“…The solubility of HCl in various imidazolium-based ILs and deep eutectic solvents (DES) has been studied in our group, and the maximum solubility can reach 0.4 g•g −1 [23][24][25][26]. The as-dissolved HCl can be directly used for the hydrochlorination of acetylene, which not only realizes its in situ utilization but also avoids intensive energy consumption in the desorption process.…”
Section: Introductionmentioning
confidence: 99%
“…28−30 We studied the absorption of HCl in DES [Emim]Cl-PEG, and the HCl solubility can reach 0.437 g•g −1 . 31 In addition, the remarkable gas solubility of [Emim]Cl 32 helps activate substrates and improve the catalytic efficiency. 33 The catalytic performance of the metals is closely related to their electron structure.…”
Section: Introductionmentioning
confidence: 99%
“…Deep eutectic solvents (DESs), IL analogues, consist of hydrogen bond acceptors (HBA) and hydrogen bond donors (HBD). They have a wide liquid range, negligible volatility, and good solubility for various substances, and are widely used in gas absorption, , extraction, and catalysts. We studied the absorption of HCl in DES [Emim]­Cl-PEG, and the HCl solubility can reach 0.437 g·g –1 . In addition, the remarkable gas solubility of [Emim]­Cl helps activate substrates and improve the catalytic efficiency .…”
Section: Introductionmentioning
confidence: 99%